The Role of Sustainability in Long Term Survival of Family Business: Henokiens Revisited - AŞKUN, OLCAY BİGE; BAKOĞLU, REFİKA (ELSEVIER SCIENCE BV, 2016)
Our previous research was designed to explore the innovation capability of the firms from the Henokiens Group surviving through ages. Now the purpose of the present study is to explore the sustainability implications of the firms in the same group by using content analysis of their websites in order to observe the role of sustainability in long-term survival of family businesses. The article proceeds in the following manner: First, we briefly review the literature. Secondly, we explore sustainability focus of firms surviving through the ages by using content analysis method. We will be analysing all firms that are listed in the www. henokiens. com. Henokiens is an association that accepts family firms which are at least 200 years of age. The 46 firms from different nationalities were analysed by content. The validity and the reliability reports and procedures are given. Finally, we provide the research findings and discuss their managerial and theoretical implications. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Sustainability; Social Sustainability; Ecological Sustainability; Long-term Survival; Henokiens group; Family Business; INSTITUTIONAL PRESSURES; STRATEGIES; FIRMS